Efeitos do sexo, do vigor e do tamanho da planta hospedeira sobre a distribuição de insetos indutores de galhas em Baccharis pseudomyriocephala Teodoro (Asteraceae) - Araújo,Ana Paula A. (2003)
Several hypotheses have been proposed to explain the patterns of host plant utilization by herbivorous insects in natural communities. We tested four hypotheses aiming to understand the pattern of attack by gall-inducing insects on the dioecious shrub, Baccharis pseudomyriocephala (Asteraceae). The shrub occurs in the Parque Estadual do Itacolomi, Southeastern Brazil, and supports ten species of galling insects. The following hypotheses were tested: i) male plants are more attacked by galling insects than female plants; ii) larger plant modules are preferentially attacked by galling insects; iii) galling insects perform better on larger modules than on smaller modules; iv) galling insects increase in abundance with meristematic availability. To address these questions, 240 plants (120 of each sex) were sampled in both reproductive and vegetative periods. We recorded the growth rate (4 cm), inflorescence and fruit production, attack rates of the galling insects, and their survivorship and mortality per shoot (module). Modules were separated into size classes (cm) and analyzed by regressions and ANCOVAs. Module size and reproductive effort were positively correlated with host plant size. We did not observe any effect of host plant gender on either variables. In the same way, host plant sex did not show any influence on the abundance and richness of galling insects. Although the abundance of galling insects showed a positive correlation with shoot size, the trend disappeared when the analyses were performed taking into consideration the number of galls per unit of growth (number of galls/cm of shoot) or biomass (number of galls/dry weight). Larval survivorship was not influenced by shoot size. Also, we observed that the abundance of one species of hemipteran galling insect showed a positive relation with leaf biomass. Therefore, we conclude that gender and vigor of this plant species do not influence the community structure of its galling herbivores.